Rationality and the study of religion - Jensen, Jeppe Sinding, 1951-; Martin, Luther H., 1937- (Routledge, 2003)
Does rationality, the intellectual bedrock of all science, apply to the study of religion?Religion, arguably the most subjective area of human behaviour, has particular challenges associated with its study. Attracting crowd-healers, conjurers, the pious and the prophetic alongside comparativists and sceptics, it excites opinions and generalizations whilst seldom explicitly staking out the territory for the discussions in which it partakes. Increasingly, scholars argue that religious study needs to define and critique its own field, and to distinguish itself from theology and other non-objectiv.